Peran Satuan Polisi Pamong Praja Dalam Menegakkan Peraturan Daerah Nomor 1 Tahun 2016 Pasal 43 Tentang Penertiban Pedagang Kaki Lima - Putra, Yogi; Sartima, Tarma; Netrivianti, Netrivianti (Jurnal Ilmiah Ekotrans & Erudisi, 2021)
The role of the Civil Service Police Unit in enforcing Regional Regulations is closely linked to the violation of Human Rights (HAM) during the enforcement process. Additionally, their supervision of Regional Regulations aligns with their primary responsibilities as enforcers of regional regulations, public order, and peace maintainers. Maintaining public peace and order is fundamental for any city, as stipulated in Regional Regulation No. 1 of 2016 in Pesisir Selatan Regency. This study employs a qualitative descriptive approach to analyze data by simply describing, explaining, and elucidating the issues regarding the enforcement of Regional Regulation No.1 of 2016, specifically Article 43, which addresses the control of street vendors in Pesisir Selatan Regency by the Civil Service Police Unit. The research findings indicate that the job of the Satpol PP in Pesisir Selatan Regency is to exercise control, organization, and enforcement in managing street sellers. (2) The challenges encountered by the Satpol PP in managing street vendors in Pesisir Selatan Regency include a lack of awareness and involvement from traders, insufficient transportation, and inadequate staff resources. (3) To address challenges in enforcing regional regulations, efforts have been made to socialize the regulations and provide more fleets and technical guidance to officers of the Civil Service Police Unit.